Study on Grouted Body Deterioration Mechanism of Sand Layer in Seawater Environment - Hongbo Wang; Zhipeng Li; Xiaoguo Wang; Qingsong Zhang; Lianzhen Zhang (Advances in Materials Science and Engineering)
Water-rich sand is a common stratum in marine underground engineering. Grouting is the most common method for solving geological disasters in water-rich sand. However, the marine environment differs greatly from the land environment. The erosion and seepage of seawater ion cause significant deterioration of grouted body, which reduces the physical and mechanical properties of grouted body. The maintenance of grouted body performance is the guarantee of long-term safe operation of the tunnel in the marine environment. In order to solve the problem of long-life grouting design for sand layer in seawater environment, an accelerated test of grouted body erosion under seawater erosion environment is designed to study the mesomorphological characteristics of seawater erosion on grouted body erosion and to reveal the mechanism of seawater erosion and solids. The evolution law of grouting plus solid strength under different slurry water-cement ratios and different seawater erosion time conditions is analyzed. The results show that the grouting plus solid effective time for water-cement ratios of 0.8 : 1, 1 : 1, 1.4 : 1, and 2 : 1 is 75a, 60a, 30a, and 15a; the index of strength degradation ratio of seawater environment to grouting plus solids is proposed, and the quantitative relationship between seawater erosion time and grouting plus solids strength is established, which provides theoretical basis for sand layer grouting reinforcement in seawater environment. We hope to provide some reference for the design and construction of sand grouting in seawater environment.